The Synthesis, Characterization, Electrochemical and Spectroelectrochemical Properties of Novel Unsymmetrical Phthalocyanines Containing Naphthoic Acid and Di-tert-butylphenoxy Groups - KOCA, ATIF (ELSEVIER SCIENCE SA, 2020)
In this study, novel A(3)B-type unsymmetrically tetrasubstituted metallo and metal free phthalocyanine compounds were synthesized by a statistical condensation method using two differently substituted precursors, 4-(6-carboxy-2-naphthoxy) phthalonitrile and 4-(2,4-di-tert-butylphenoxy) phthalonitrile. The structures of the synthesized phthalocyanine compounds (ZnPc, CuPc, CoPc, NiPc and H2Pc) were characterized with spectroscopic techniques of FT-IR, UV-Vis, H-1-NMR, MALDI-TOF MS and elemental analysis. Electrochemistry of metallophthalocyanines (MPcs) was studied and electrochemical responses were compared with each other in order to understand the influence of the cations in the Pc core and substituent environment to the redox responses of them. Electrochemical characterizations indicated that one metal based reduction and one metal based oxidization processes were observed with CoPc in addition to the Pc based electron transfer reactions. Moreover ZnPc, CuPc, NiPc, and H2Pc only indicated Pc ring based redox couples. Extraordinarily, all complexes were electrodeposited on the working electrode surface during the reduction reactions which intensively altered the redox behaviors of the complexes. In situ spectroelectrochemical characterizations supported the voltammetric assignments and indicated electrocheromic functionality of the complexes. ZnPc was tested as potential dye for DSSCs and illustrated reasonable photovoltaic performance.
Keywords: Synthesis; unsymmetrical; phthalocyanine; carboxyl; electrochemistry; spectroelectrochemistry; IN-SITU SPECTROELECTROCHEMISTRY; ZINC PHTHALOCYANINES; SUBSTITUTED PHTHALOCYANINES; COBALT PHTHALOCYANINE; SPECTRAL PROPERTIES; METAL-FREE; METALLOPHTHALOCYANINES; SPECTROSCOPY; MANGANESE; IRON